Four-class drug-resistant HIV-1 subtype C in a treatment experienced individual on dolutegravir-based antiretroviral therapy in Botswana. (24th August 2018) - Seatla, Kaelo K.; Avalos, Ava; Moyo, Sikhulile; Mine, Madisa; Diphoko, Thabo; Mosepele, Mosepele; Gaolatlhe, Tendani; Rowley, Christopher F.; Ramaabya, Dinah; Jarvis, Joseph N.; Kasvosve, Ishmael; Gaseitsiwe, Simani
Abstract : N/A: There are limited data on the effectiveness of dolutegravir (DTG)-based combination antiretroviral therapy (ART) in real-life settings in southern Africa where HIV-1 subtype C predominates. We report a patient infected with HIV-1 subtype C on DTG-based ART previously exposed to raltegravir who developed multidrug resistance mutations to four antiretroviral classes. There is need for drug resistance monitoring and clinical vigilance to ensure effectiveness of HIV treatment programs even in the era of DTG-based ART.